2004
DOI: 10.1080/15287390490273479
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage to Nuclear DNA in Hyperthyroid Rat Liver: Inability of Vitamin C to Prevent the Damage

Abstract: The effects of hyperthyroidism on oxidative DNA damage in liver tissue and modification by vitamin C supplementation were investigated in rats. Animals were rendered hyperthyroid by administration of L-thyroxine (0.4 mg/100 g food) for 25 d. In the plasma samples, T(3), T(4), and thyroid-stimulating hormone (TSH) were measured by radioimmunoassay and ascorbate spectrophotometrically. Oxidative damage to hepatic nuclear DNA was determined by measuring deoxy-guanosine (dG) and 8-oxodG by high-performance liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In addition, Kupffer cells isolated from acutely T 3 -treated rats exhibited upregulation of UCP2 mRNA, which may limit mitochondrial ROS production by these cells (30). Consequently, T 3 -induced ROS production is associated with diminution in antioxidant defenses (28,(31)(32)(33), thus increasing the oxidative stress status in the liver with enhancement of hepatic lipid peroxidation (22,28,(34)(35)(36), protein carbonylation (37), and DNA oxidation (38). This pro-oxidant state induced in the liver of experimental animals by thyroid hormone administration is considered as a mild redox alteration, considering the lack of occurrence of morphological changes in liver parenchyma, except for significant hyperplasia and hypertrophy of Kupffer cells ( Fig.…”
Section: T 3 -Induced Enhancement Of Liver O 2 Consumption and Oxidatmentioning
confidence: 99%
“…In addition, Kupffer cells isolated from acutely T 3 -treated rats exhibited upregulation of UCP2 mRNA, which may limit mitochondrial ROS production by these cells (30). Consequently, T 3 -induced ROS production is associated with diminution in antioxidant defenses (28,(31)(32)(33), thus increasing the oxidative stress status in the liver with enhancement of hepatic lipid peroxidation (22,28,(34)(35)(36), protein carbonylation (37), and DNA oxidation (38). This pro-oxidant state induced in the liver of experimental animals by thyroid hormone administration is considered as a mild redox alteration, considering the lack of occurrence of morphological changes in liver parenchyma, except for significant hyperplasia and hypertrophy of Kupffer cells ( Fig.…”
Section: T 3 -Induced Enhancement Of Liver O 2 Consumption and Oxidatmentioning
confidence: 99%
“…3,3 , ,5-Triiodothyronine (T3)-induced pro-oxidant activity (i) occurs at mitochondrial (Fernández & Videla 1993a), microsomal (Fernández et al 1985), and cytosolic (Huh et al 1998) levels, (ii) involves generation of reactive nitrogen species (RNS) in addition to ROS (Fernández et al 1997), and (iii) accounts for 16-25% of the net increase in total O 2 consumption of the liver (Fernández & Videla 1993b). The latter respiratory component may include O 2 equivalents employed both in ROS/RNS generation and in the free radical-dependent oxidation of unsaturated fatty acids (Fernández et al 1985, Landriscina et al 1988, Venditti et al 1997, Huh et al 1998, proteins (Tapia et al 1999), and DNA (Andican et al 2004). Enhancement in liver mitochondrial H 2 O 2 production is also observed in the transition from hypothyroid to hyperthyroid state as a function of the content of autoxidisable electron carriers (Venditti et al 2003), an effect that is mimicked by cold-induced hyperthyroidism (Venditti et al 2004).…”
Section: Superoxide Radical (Omentioning
confidence: 99%
“…Ultrastructural and functional changes in hepatocyte mitochondria have been documented in rats who are thyrotoxic, 7 including T 3 associated mitochondrial-induced apoptosis and oxidative hepatic deoxyribonucleic acid damage because of lipid peroxidation, protein oxidation, and glutathione depletion. 7,8 Feline studies have shown that the bone alkaline phosphatase (ALP) isoenzyme is high in the serum of cats with hyperthyroidism and that both the liver and bone isoenzymes contribute to the high ALP activity in the serum of cats with hyperthyroidism. 9,10 Although increases in serum activity of liver-derived enzymes are well documented in cats with hyperthyroidism, the degree of enzyme increase, changes in liver function, serum ammonia concentration, and hepatic ultrasonographic appearance are not documented.…”
mentioning
confidence: 99%